Digital teaching competence of university teachers: A comparative study at two European universities - Sánchez-Caballé, Anna; Esteve-Mon, Francesc Marc (Australasian Journal of Educational Technology, 2022)
This study analysed the level of digital competence of 910 university teachers at one Spanish and one Polish university, using a self-perception questionnaire based on the DigCompEdu framework. For this purpose, a quantitative methodology was used with the aim of finding out the situation at both institutions through focusing on gender, professional category, and areas of knowledge of the participants. The results showed that the university teachers generally perceived themselves as having an intermediate level of digital competence. In this sense, it was observed that the elements selected for analysis (university, gender, and professional category) can have direct implications for the results and that there are significant differences depending on the group to which they belong. Implications for practice or policy: Digital teaching competence need to be improved in the university context. Gender influences the self-perceived level of digital teaching competence and this needs to be considered in the university practices and policies. University teachers at the levels of junior lecturer and teaching assistant show better digital teaching competence and this needs to be considered in the university practices and policies.